Amtsal Al-Qur’an sebagai metode komunikasi wahyu dan pendidikan Islam: Perspektif ulumul Qur’an - Nailah Ramadhani; Afifa Lutfiahtul Hasanah; Aldiansyah Saputra; Riska Sawitri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
The Qur’an not only serves as a source of law and creed but is also rich in educational values and effective communication methods. One prominent method of delivering messages is the use of amsal or parables. This study aims to examine the concept of amsal in the Qur’an, explain its types, and analyze its rhetorical and educational functions in the context of learning and divine communication. The main issues addressed include how amsal is understood from the perspective of Ulumul Qur’an and its relevance in modern life. The research uses a qualitative descriptive approach with library research, involving a review of books, journals, scholarly articles, and online documentation related to Qur’anic amsal. The findings indicate that amsal is a divine communication strategy that bridges abstract concepts with concrete illustrations, reinforces doctrinal messages, fosters moral and spiritual awareness, and engages intellectual and emotional dimensions simultaneously. The Qur’an’s amsal are categorized into musarrahah, kaminah, and mursalah, each with distinct characteristics and functions. These results confirm that amsal is not merely a rhetorical ornament but a methodological foundation relevant for developing communicative, reflective, and transformative Islamic education.